Reduced Hepatic Carcinoembryonic Antigen-Related Cell Adhesion Molecule 1 Level in Obesity - Heinrich, Garrett; Muturi, Harrison T.; Rezaei, Khadijeh; Al-Share, Qusai Y.; DeAngelis, Anthony M.; Bowman, Thomas A.; Ghadieh, Hilda E.; Ghanem, Simona S.; Zhang, Deqiang; Garofalo, Robert S.; Yin, Lei; Najjar, Sonia M. (Frontiers in Endocrinology, 2017)
Impairment of insulin clearance is being increasingly recognized as a critical step in the development of insulin resistance and metabolic disease. The carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) promotes insulin clearance. Null deletion or liver-specific inactivation of Ceacam1 in mice causes a defect in insulin clearance, insulin resistance, steatohepatitis, and visceral obesity. Immunohistological analysis revealed reduction of hepatic CEACAM1 in obese subjects with fatty liver disease. Thus, we aimed to determine whether this occurs at the hepatocyte level in response to systemic extrahepatic factors and whether this holds across species. Northern and Western blot analyses demonstrate that CEACAM1 mRNA and protein levels are reduced in liver tissues of obese individuals compared to their lean age-matched counterparts. Furthermore, Western analysis reveals a comparable reduction of CEACAM1 protein in primary hepatocytes derived from the same obese subjects. Similar to humans, Ceacam1 mRNA level, assessed by quantitative RT-PCR analysis, is significantly reduced in the livers of obese Zucker (fa/fa, ZDF) and Koletsky (f/f) rats relative to their age-matched lean counterparts. These studies demonstrate that the reduction of hepatic CEACAM1 in obesity occurs at the level of hepatocytes and identify the reduction of hepatic CEACAM1 as a common denominator of obesity across multiple species.